Digital Health Communication Strategy through TikTok: Content Analysis and Audience Response on the @tirtaaaa Account - Hasanatul Mardliyah Br Tambunan; Erwan Efendi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study analyzes the role and strategies of digital health communication through TikTok as an effective medium for disseminating health information, with a focus on the TikTok account of Dr. Tirta (@tirtaaaa). A qualitative approach was applied, employing content analysis of health education videos alongside audience response analysis drawn from the comments section. The data set comprised 30 health education videos uploaded between January and March 2025, with approximately 500 comments selected through purposive sampling. The results indicate that a communication strategy emphasizing plain language, a persuasive style, source credibility, and engaging visuals proved most effective in raising audience engagement and comprehension. Audience response analysis revealed that approximately 80–85% of comments were positive, characterized by expressions of support, appreciation, and reported behavioral shifts toward a healthier lifestyle, while the remaining comments consisted of neutral responses and criticism. These findings suggest that strategically managed health communication through TikTok can broaden public awareness of health-related matters. This study also identified potential adverse effects of social media use, including the circulation of misinformation and misinterpretation of health messages when content is not delivered responsibly. The findings confirm that TikTok can serve as an effective health communication medium when supported by appropriate, ethical, and digital literacy-based communication strategies. The study carries practical implications for health practitioners, content creators, and policymakers seeking to utilize social media as a channel for public health education.